1999
DOI: 10.1046/j.1464-5491.1999.00115.x
|View full text |Cite
|
Sign up to set email alerts
|

Contra‐indications to metformin therapy are largely disregarded

Abstract: Despite the considerable risk of lactic acidosis in the majority of patients, no cases were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
86
0
7

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 21 publications
8
86
0
7
Order By: Relevance
“…Furthermore, development of contraindications rarely results in discontinuation of metformin therapy [16]. These data have been confirmed in several other studies in various countries [17,18]. Despite this, lactic acidosis remains rare [8], even if case reports still continue to be published regularly [9,19].…”
Section: Introductionmentioning
confidence: 80%
“…Furthermore, development of contraindications rarely results in discontinuation of metformin therapy [16]. These data have been confirmed in several other studies in various countries [17,18]. Despite this, lactic acidosis remains rare [8], even if case reports still continue to be published regularly [9,19].…”
Section: Introductionmentioning
confidence: 80%
“…Moreover, both retrospective population-based studies [12] and studies in selected cohorts [10,11,13,14,35,36] showed that the currently proclaimed contraindications and precautions for metformin therapy are frequently disregarded (Table 2). Interestingly, among the ∼2,500 patients followed in these studies only one case of lactic acidosis was reported, and even this one case could not be causally attributed to metformin since it was associated with intercurrent myocardial infarction and renal failure [12].…”
Section: Disregard Of Metformin Contraindications and Incidence Of Lamentioning
confidence: 99%
“…There is no evidence that old age should in itself be a reason to withhold metformin. It is important to point out, however, that 'hard' contraindications are far more likely to emerge in the elderly [11] than in the young, and these should therefore be regularly monitored.…”
Section: Suggested Modifications Of Metformin Contraindicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…More impressively, in case of HF it may prolong survival for up to 2 years [17]. This is important, given that 10 --25% of T2DM patients receiving metformin may suffer from HF [50][51][52].…”
Section: Expert Opinionmentioning
confidence: 99%